2008
DOI: 10.1177/147323000803600414
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Hepatic Differentiation of Mesenchymal Stem Cells from Human Fetal Bone Marrow

Abstract: We examined whether human fetal mesenchymal stem cells (FMSCs) derived from fetal bone marrow were able to differentiate into functional hepatocyte-like cells in vitro. The surface phenotype of FMSCs was characterized by flow cytometry. To induce hepatic differentiation of FMSCs, we added hepatocyte growth factor, basic fibroblast growth factor and oncostatin M into the cell culture medium. After 21 days of hepatocyte induction, FMSCs expressed the hepatocyte-specific markers, alpha-fetoprotein and cytokeratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Wells et al (1997) also demonstrated pericellular C-18 staining in rabbit and human liver sections, while the presence of C-18 on the cell surface of HepG2 cells was confirmed with radiolabeled antibodies. In the present study, 3-D encapsulated HepG2 cells were positive for C-18 over the 10-day culture period and thus retain this liver-specific feature, in line with several reports where the expression of this hepaticspecific marker is examined (Nakamishi et al 2002;Wei et al 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Wells et al (1997) also demonstrated pericellular C-18 staining in rabbit and human liver sections, while the presence of C-18 on the cell surface of HepG2 cells was confirmed with radiolabeled antibodies. In the present study, 3-D encapsulated HepG2 cells were positive for C-18 over the 10-day culture period and thus retain this liver-specific feature, in line with several reports where the expression of this hepaticspecific marker is examined (Nakamishi et al 2002;Wei et al 2008).…”
Section: Discussionsupporting
confidence: 89%
“…90 Fetal BM-derived MSCs are able to differentiate into functional hepatocyte-like cells and may serve as a source of cells for liver disease therapy. 91 After hepatocyte induction, fetal MSCs expressed the hepatocyte-specific markers, α-fetoprotein, and cytokeratin 18, as demonstrated by immunofluorescence staining. They also demonstrated in vitro functions characteristic of liver cells, including albumin production, urea secretion, and glycogen storage.…”
Section: Use Of Embryonic Stem Cellsmentioning
confidence: 98%
“…They also demonstrated in vitro functions characteristic of liver cells, including albumin production, urea secretion, and glycogen storage. 91 The use of human liver progenitor or stem cells from fetus abrogates the issue of forced differentiation as in the case of induced pleuripotent cells, as fetal progenitors have undergone sufficient morphological and physiological differentiation so that they are committed to a hepatic fate, and yet they retain their 'stemness' by maintaining their bipotentiality, proliferative capacity, and transplantability.…”
Section: Use Of Embryonic Stem Cellsmentioning
confidence: 99%
“…Hepatic induction starts following an FGF signal, that AT-MSC Using Dexa, ascorbic acid, EGF, bFGF, and HGF Gene expression analysis, functional assays, and transplantation into mouse with chronic liver injury [17] AT-MSC FGF, EGF, HGF, OSM, Dexa, and TSA Hepatocyte-specific markers (ALB and AFP), bioactivity assays (LDL uptake and glycogen storage) [18] UC-MSCs Sequential exposure to EGF, bFGF, bFGF-HGF, and finally OSM Analyzed HLCs by reverse-transcription polymerase chain reaction, flow cytometry, and immunocytochemical assays [19] UC-MSCs Sequential exposure to TSA or DMSO Morphology and protein expression, urea synthesis, ammonia concentration [20] UC-MSCs One-step protocol by using HGF and FGF-4 ALB, AFP, and CK-18, LDL uptake, and glycogen storage [21] UC-MSCs Emphasizing on the critical role of OSM Function of differentiated cell by PAS staining and LDL uptake was examined. The protein expressions of TP, ALB, GLB, BUN, and AFP were also detected [22] UCB-MSCs HGF and FGF-4 Urea production and protein secretion and production of AFP and ALB [2] umbilical cord vein MSCs Two-step protocol that contained HGF and OSM Liver-specific protein markers such as ALB and CK-18 and expression of transthyretin, glucose 6-phosphatase, CK-18,18, AFP, hepatocyte nuclear factor-3β and ALB, indocyanine green cell uptake, glycogen storage [23] F-MSCs HGF, bFGF, and OSM Measured the expression of hepatocyte-specific markers such as AFP and CK-18 [24] BM-MSCs FGF-4, HGF, and combination of HGF-ITS-Dexa, and TSA Glycogen storage and CK-18 expression, HNF-3beta, AFP, CK18, ALB, HNF1α, MRP2 and C/EBPα, ALB secretion, urea production and P450 (CYP)-dependent activity [25] Afshari et al activates the RAS/MAPK pathway. Several FGFs (FGF1, 2, 8, and 10) are detected in the cardiac mesoderm during the beginning steps of hepatogenesis [38].…”
Section: The Molecular Embryogenesis Of the Livermentioning
confidence: 99%